2014
DOI: 10.1007/s00707-014-1136-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary vibration on the frictional behavior of a dense sheared granular layer

Abstract: We report results of 3D Discrete Element Method (DEM) simulations aiming at investigating the role of the boundary vibration in inducing frictional weakening in sheared granular layers. We study the role of different vibration amplitudes applied at various shear stress levels, for a granular layer in the stick-slip regime and in the steady-sliding regime. Results are reported in terms of friction drops and kinetic energy release associated with frictional weakening events. We find that larger vibration amplitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…To further characterize vibration-induced shear weakening and dynamic triggering, and to identify intervals of increased seismic hazard, it will be useful to investigate the effect of varying the noise strength ρ as well as the vibration amplitude and frequency. Ferdowsi et al [10,11] have found in their simulations evidence of an amplitude threshold below which vibrations do not cause significant frictional weakening. It will be interesting to examine if the STZ theory can capture this observation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To further characterize vibration-induced shear weakening and dynamic triggering, and to identify intervals of increased seismic hazard, it will be useful to investigate the effect of varying the noise strength ρ as well as the vibration amplitude and frequency. Ferdowsi et al [10,11] have found in their simulations evidence of an amplitude threshold below which vibrations do not cause significant frictional weakening. It will be interesting to examine if the STZ theory can capture this observation.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of granular earth materials, an important example of phenomena observed in nature and in simulations, and captured in the present STZ model, is the dynamic triggering of catastrophic events [10,11,19,49], known to occur in the presence of a granular gouge layer. Specifically, we found that vibrations reduce the shear strength and clock-advance the first slip event upon loading.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations